TINGKAT PENGETAHUAN IBU TERHADAP PEMBERIAN SUSU FORMULA PADA BAYI USIA 0–6 BULAN DI LINGKUNGAN IX KELURAHAN BANDAR SELAMAT KECAMATAN MEDAN TEMBUNG - Elvalini Warnelis Sinaga (Jurnal Ilmiah Kebidanan Imelda, 2021)
Formula milk is milk made from cow's milk or artificial milk whose composition is changed so that it can be used as a substitute for breast milk. Formula milk is a substitute for breast milk or can also complement breast milk. But it must be remembered that none of the nutritional compositions can match breast milk. The purpose of this study was to better understand and know the advantages and disadvantages of giving formula milk to infants. This research is descriptive using primary data by distributing questionnaires and tabulating to get the results. The population in this study were all mothers in Ward IX, Bandar Selamat Subdistrict, Medan Tembung Subdistrict with a total population of 30 respondents and using a total sampling technique of 30 respondents. From the results of the study, it is known that the majority have less knowledge as many as 15 respondents (50%), based on education the majority have less knowledge in junior high schools as many as 8 respondents (27%), based on work the majority have less knowledge in IRT as many as 11 respondents (37%), and based on sources of information the majority of knowledgeable people do not get information from electronic media as many as 8 respondents (26%). Based on the results of the study, it can be concluded that the mother's level of knowledge on formula feeding in infants aged 0-6 months is in the poor category. Therefore, knowledge greatly influences mothers to achieve the Exclusive Breastfeeding program. Therefore, it is hoped that mothers can increase their knowledge about the advantages and disadvantages of formula feeding.